Patient reported experience measures: an assessment of the in-patients in a tertiary care teaching hospital - Yathindra, Chitra; Saldanha, Alvita Lurdin (International Journal Of Community Medicine And Public Health, 2024)
Background: The key factor that helps the healthcare industry stand out from its competitors is identifying the needs of patients and taking timely measures to meet those needs. One such factor in identifying patient needs is assessing the experience of the patients that has been reported. This study aims to assess the level of patient reported experience measures of the inpatient level in a tertiary care teaching hospital and also to identify the determinants affecting patient experience. Methods: This study used questionnaires to get information from 997 in-patients about the level of patient experiences in the chosen tertiary care teaching hospital. The study was conducted between 1st January 2023 to 31st January 2023. Results: The study showed that more than 60% of the respondents opined they strongly agreed that their experience with doctors and nurses was good. More than 50% of the respondents had a good experience with regards to billing services. This study has attempted to identify various aspects that measure patient experience and has suggested measures to improve the patient satisfaction. Conclusions: The expectations that a patient has from the healthcare sector and the instances where the healthcare sector meets those expectations play a crucial role in determining the success of a healthcare institute. This study suggested various measures to be undertaken in order to improve the patient satisfaction based on the patient reported experiences.